2020
DOI: 10.1080/16070658.2020.1733305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity among selected schoolchildren and adolescents in Cofimvaba, South Africa

Abstract: Background: Childhood obesity has become a growing global epidemic. In South Africa, overweight and obesity during childhood and adolescence are rising. The objectives of this study were (i) to estimate the prevalence of overweight and obesity among selected students in Cofimvaba, a rural settlement in Eastern Cape province, South Africa, and (ii) to assess the accuracy of the mid-upper arm circumference (MUAC) and ultrasound triceps skin-fold thickness (TSF) methods of predicting these health parameters Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…This was very evident in the age range 15 to 17 years. This finding was corroborated by other workers [14]- [16], [20], [24], [26], [31]. This could be explained by the fact that the girls consumed more calories, being more involved in culinary chores and also were more sedentary in nature.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was very evident in the age range 15 to 17 years. This finding was corroborated by other workers [14]- [16], [20], [24], [26], [31]. This could be explained by the fact that the girls consumed more calories, being more involved in culinary chores and also were more sedentary in nature.…”
Section: Discussionsupporting
confidence: 86%
“…The combined prevalence of obesity and overweight was 9.8% (1.0% and 8.8% respectively), was not overly at variance with other studies from Nigeria [11]- [13], where the prevalence varied from rural to urban areas, and across various ethnic groups, rural youths being less obese than the urban. The prevalence of obesity and overweight was lower in these students compared to findings from South Africa [14]- [16], India [17], China [18], Saudi Arabia [19], [20], South America [21]- [24], Europe [25]- [27] and North America [28], [29]. This may be partly accounted for by the fact that these studies neither segregated public from private schools [17], [30] nor affluent [31] from the less endowed.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For example, between 2000 and 2013, overweight and obesity increased from 11 to 19% in southern African countries, whereas the prevalence of stunted children remained almost the same [2]. In 2020, approximately 17% of the children between age 5 and 19 in South Africa presented with overweight and obesity [3], which was estimated at 19% for all children under age 19 in Ghana [4]. In general, it is often reported that more girls tend to have overweight or obesity compared to boys [5].…”
Section: Introductionmentioning
confidence: 99%
“…The second layer of youth susceptible to hot climate is young girls with obesity. In South Africa, 13.5% of young people are estimated to be overweight and obese (O/O) [ 32 ]. The burden of O/O induces heat stress, as body fatness determines one’s heat tolerance level.…”
Section: Resultsmentioning
confidence: 99%